Interfaces da avaliação externa no currículo escolar: percepções de professores de uma escola da rede municipal - Grenzel, Fabiana Boff (2022)
The present dissertation of the Professional Master's Course in Public Policies and Educational Management, of the Graduate Program, of the Public Policy Research Line, addresses the issue of external evaluation in the educational context. Its general objective was to understand the implications of external evaluation on the curriculum and school learning of students in the 5th year of Elementary School I. Specifically, it sought to recognize the conceptions and policies related to external evaluation; to analyze the role of the pedagogical coordinator of Elementary School in relation to the referrals of the evaluation process and the school curriculum for students of the 5th year of Elementary School I; examine the relationship between assessment, curriculum and learning of students in the 5th year of Elementary School I. The research has a qualitative approach and is characterized as a case study, for which a bibliographic investigation and field research were carried out, carried out in a Public School, with a pedagogical coordinator of Elementary School I and four teachers of the 5th year of Elementary School I, for which an open questionnaire was used as an instrument. It was observed that, in the understanding of the research participants, external evaluations produce a competitive perspective between schools, since the evaluation results make up the IDEB index. For the participants, external assessments do not cover the entire development of the student, since there are skills and competences that go beyond the formal curriculum and are revealed in the real curriculum. In this bias, the importance of evaluations being in line with the school curriculum was highlighted. On the other hand, it was understood that external evaluations serve as subsidies for pedagogical practices, through the possibility of reflecting on the work developed by the subjects involved in education, highlighting the need to review contents that were not well assimilated and instigating the search for new pedagogical practices. The educational product consisted of a proposal for continuing education carried out with teachers and managers, whose purpose is the theoretical and practical deepening of external assessments. Thus, we propose the analysis of one of the evaluations used in the school (Saeb), seeking to interpret what they point to, then formulate together with the teachers what is possible to propose in relation to the results obtained, aiming at the development of the students. It is understood that the present investigation can contribute to the professional development of education actors, aiming, through external evaluations, possibilities for growth and important work subsidies, overcoming a negationist and contrary view about external evaluations that still persists on the part of of many educators.